The assessment of serum Zinc, Testosterone Concentration and sperm quality in Infertile Males (Journal of Academic Research, 2023)
Background: Male infertility is frequently caused by low sperm production or motility challenges. Zinc performs a major function in the biology of spermatogenesis in males. Objective: The aim of this paper was to evaluate serum zinc, testosterone concentrations, and several sperm parameters in infertile men. Methods: Sixty-four infertile males, ages ranging from 22 to 45 years, were enrolled in an infertility treatment center in Misrata, Libya. WHO guidelines were used to examine the sperm samples. Serum zinc concentration was determined by a photometric method, while serum testosterone was determined by a chemiluminescence immunoassay method. Result: Infertile males have significantly lower serum zinc and testosterone concentrations than fertile men. Serum zinc was lower in infertile patients who had a low sperm count, weak sperm motility, and abnormal morphology. Conclusion: Zinc has a considerable impact on a variety of sperm parameters and testosterone concentration. The result indicates that estimating serum zinc levels may help to improve the investigation and treatment of infertile males.